2022
DOI: 10.1111/1346-8138.16661
|View full text |Cite
|
Sign up to set email alerts
|

Clinical value of the prognostic nutritional index and red blood cell distribution width‐to‐albumin ratio for the prediction of severity of and mortality associated with Stevens–Johnson syndrome/toxic epidermal necrolysis

Abstract: The prognostic nutritional index (PNI) and red blood cell distribution width-to-albumin ratio (RAR) are considered to be related to the prognosis of disease severity. However, the role of these biomarkers in predicting Stevens-Johnson syndrome/toxic epidermal necrolysis (SJS/TEN) severity and mortality is unclear. The aim of the current study was to investigate the association of PNI and RAR with severity and mortality in individuals with SJS/TEN. Clinical data were retrospectively collected from 74 individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“… 15 Another study revealed that RDW/Alb could be a meaningful biomarker to assess the severity of SJS/TEN. 16 However, there have been no studies showing the role of RDW alone in the prognosis of SJS/TEN. In this study, RDW-SD47.9 fL and PCT > 0.67 ng/mL were screened out as significant risk factors for in-hospital death from the meaningful indicators of univariate analysis, which can partly corroborate these findings in the appeal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 15 Another study revealed that RDW/Alb could be a meaningful biomarker to assess the severity of SJS/TEN. 16 However, there have been no studies showing the role of RDW alone in the prognosis of SJS/TEN. In this study, RDW-SD47.9 fL and PCT > 0.67 ng/mL were screened out as significant risk factors for in-hospital death from the meaningful indicators of univariate analysis, which can partly corroborate these findings in the appeal.…”
Section: Discussionmentioning
confidence: 99%
“… 9 10 Other factors that may affect the prognosis of SJS/TEN include chronic kidney disease (CKD), 11 tuberculosis, 12 septicemia, 13 complications of respiratory disorder, 14 etc . In addition, the role of new inflammatory markers, such as red cell distribution width to hemoglobin ratio (RDW/Hb), 15 red blood cell distribution width to albumin ratio (RDW/Alb), 16 and neutrophil to lymphocyte ratio, 17 in the prognosis of SJS/TEN is also a research hotspot in recent years. However, due to the rarity of SJS/TEN and the heterogeneity of the studies, clinical risk factors for its mortality remain unclear.…”
Section: Introductionmentioning
confidence: 99%